Pelatihan Bahasa Inggris Pada Pedagang Kain Tenun Di Desa Pringgasela Melalui Direct Selling - Fathurrahman Imran; Aprianoto Aprianoto; Komang Dedy Sandiarsa; Muhammad Muhlisin; Muhammad Asrul Hasby; Edi Firman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
Pringgasela is one of the tourism places in Lombok island which is located at Pringgasela Sub-district, East Lombok Regency. Pringgasela has been announced as a Fabric Industry Centre in Lombok island, the best quality of fabrics is produced by the fabric craftsmen and craftswomen in that place, this fabric industry is important to support the local economic system of Pringgasela’s society. Foreign tourists are the target market of the fabric sellers in global scale; however, this opportunity was not supported by the English communication skill of the sellers. This program is aimed to train and facilitate the fabric craftsmen, craftswomen and the fabric sellers of English communication skill by using Direct Selling gradually and continuously, so they could improve their skill in English communication, especially in promoting their products. Technically, the objectives of this program were; 1). to train the the fabric craftsmen, craftswomen and the fabric sellers of English communication skill, so they could promote their products to the foreign tourists effectively and efficiently; 2). as the alternative solution for the fabric sellers, in which they would not rely their target profit to the local guide or travel agency anymore. The method of this program has been done through four steps; 1). Planning; 2). Action; 3). Guiding; and 4). Reflection and Evaluation. During the process of the program, the trainers team monitor the participants by interviewing them related with the material, the method used and the tutors of this program. Generally, the participants gave a positive response, they stated that this program was a good training program and the materials given were appropriate for them that clearly explained by the professional tutors. Based on the calculation data, the responses of the participants were; 1) 83% (very good category); 2). 8% (good category); 3). 8% (enough category); and 4) 0% (less category).